2008
DOI: 10.1111/j.1524-475x.2008.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen attenuates cell growth in skin fibroblasts cultured in a high‐glucose medium

Abstract: Hyperglycemia and hypoxia synergistically retard diabetic wound healing. We investigated the direct effect of hyperbaric and normobaric hyperoxia on skin fibroblasts cultured in a high-glucose medium. Detroit 551 human dermal fibroblasts cultured in Dulbecco's modified Eagle's medium containing d-glucose had reduced cell survival compared with cells grown in normal glucose medium; survival was 27.5+/-3.8% lower in 25 mM glucose and 30.6+/-3.7% lower in 50 mM glucose. Cell survival decreased because of inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Decreased fibroblast proliferation. While it has been reported that the rate at which diabetic fibroblasts proliferate is not significantly lower than that of normal fibroblasts (Lerman et al, 2003), some authors claim that delayed and decreased fibroblast proliferation is a characteristic feature of nonhealing wounds (Moore et al, 1997;Enoch and Price, 2004;Lin et al, 2008). In Eq.…”
Section: The Impact Of Diabetes On the Wound Healing Environmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Decreased fibroblast proliferation. While it has been reported that the rate at which diabetic fibroblasts proliferate is not significantly lower than that of normal fibroblasts (Lerman et al, 2003), some authors claim that delayed and decreased fibroblast proliferation is a characteristic feature of nonhealing wounds (Moore et al, 1997;Enoch and Price, 2004;Lin et al, 2008). In Eq.…”
Section: The Impact Of Diabetes On the Wound Healing Environmentmentioning
confidence: 97%
“…Oyibo et al (2001) state that the outcome of diabetic foot ulcers is influenced by (at least) blood supply and the presence of infection. An adequate oxygen supply is essential for healing and an inadequate oxygen supply is often reported as a cause of wound chronicity (Hunt et al, 1967(Hunt et al, , 1969Sen et al, 2002;Said et al, 2005;Hopf et al, 2006;Lin et al, 2008). We model decreased oxygen supply by reducing the parameter λ 5 in Eq.…”
Section: The Impact Of Diabetes On the Wound Healing Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hyperbaric oxygen treatment at 3 atm roughly triples the oxygen diffusion between the capillaries and tissue (Grolman et al 2001). However, the increased level of oxygen also creates the risk of oxygen toxicity, but the effects can be minimized if the oxygen is breathed intermittently for 60-120 min (Lin et al 2008). Topical oxygen also has the advantages of using a portable device, being less expensive and delivering oxygen directly to the wound without the dependence of a vascular network (unless hyperbaric oxygen is delivered in a monoplace chamber).…”
Section: (B) From Experiments To Patientsmentioning
confidence: 99%
“…The increased pressure (in contrast to normobaric treatment) creates a steeper pressure gradient, which helps the supplemental oxygen reach the cells (Lin et al 2008). For example, hyperbaric oxygen treatment at 3 atm roughly triples the oxygen diffusion between the capillaries and tissue (Grolman et al 2001).…”
Section: (B) From Experiments To Patientsmentioning
confidence: 99%